Association between professional qualification and adverse events in neonatal and pediatric intensive treatment units - Eliane Cristina Sanches Maziero; Elaine Drehmer de Almeida Cruz; Josemar Batista; Francine Taporosky Alpendre; Marilise Borges Brandão; Elias Teixeira Krainski (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: to verify the association between the qualification of nursing professionals and the occurrence of adverse events in neonatal and pediatric intensive care units. Method: Cross-sectional and evaluation study conducted in six intensive care units of five public hospitals in the state of Paraná, Brazil. Data was collected from April/2017 to January/2018 through the use of a questionnaire to be completed by 143 nursing professionals and retrospective analysis of 79 medical records using the Neonatal Trigger Tool and Pediatric Trigger Tool instruments. The prognostic factors were professional training and the existence, or not, of a continuing education service; analysis was performed by logistic regression. Results: Detected 30 adverse events in 22 medical records analyzed. There was a prevalence of infection (n = 12; 40%) and skin damage (n = 9; 30%). Among the prognostic factors, continuing education was identified as a protective factor against adverse events (p≤0.05). Conclusion: Continuing education was associated with the prevention of adverse events in neonatal and pediatric intensive care units.